Sex differences in skill, performance, and injury in surfing: A scoping review - Melville, J.; Forsyth, J. R.; Paikin, R.; Constantniou, M. (Journal of Sports Sciences, 2026)
Surfing is increasing in popularity with rising professionalism in the sport. While sex-specific differences in skill, physical performance, and injury profiles are recognised across various sports, their presence in surfing remains unclear. This review collates the available evidence on sex-specific skill, physical performance, and injury profiles in surfers, to explore any evidence gaps and to recommend focus areas for future research. Five databases (Scopus, Web of Science, CINAHL Complete, SPORTDiscus, and MEDLINE Complete) were searched from inception to November 2025. Studies that investigated surfing skill, physical performance or injury profiles in both male and female participants were included. Of 4729 studies identified, 50 met the inclusion criteria. These included 10 studies on surfing skills, 17 on physical performance, and 32 on injury profiles. Studies included outcome measures with sex-specific comparisons for skill (70%), physical performance (64%) and injury (19%). Overall, sex comparisons were made consistently in five (14%) outcome measures across all study concepts. Limited research on sex-specific injury profiles restricts the development of injury prevention strategies for female surfers. As the literature evolves in surfing, researchers should maximise the value of their data by reporting on sex-specific differences, appropriately normalising values (where necessary) and utilising consistent testing approaches.